Effects of Quality Improvement Education in Diabetic Retinopathy on Routine Clinical Practice Patterns of Optometrists. Issue 11 (November 2020) - Maatouk, Christopher M.; Hentati, Firas; Urbano, Catherine A.; Greenlee, Tyler E.; Conti, Thais F.; Hom, Grant L.; Immler, Wes K.; Babiuch, Amy S.; Singh, Rishi P.
Abstract : SIGNIFICANCE: Optometrists play a preventive role in diabetic care by detecting early signs of diabetic retinopathy (DR), a leading cause of blindness in adults. This study demonstrates that additional training can improve optometrists' ability to assess the presence and severity of DR in individuals with diabetes. PURPOSE: This study aimed to determine the impact of a quality improvement intervention involving education, assessment, and feedback on improving the evaluation and referral patterns of optometrists with regard to their patients with diabetes. METHODS: A pre-interventional and post-interventional analysis of optometrist practices was conducted through a retrospective chart review of diabetic patient encounters from July 2018 to March 2019. Dilated fundus examination (DFE) documentation, follow-up scheduling, referral practices, and usage of various imaging modalities were collected from patient records. Concordance of DR severity recordings between DFE findings, assessment and plan notes, and International Classification of Diseases codes was calculated. RESULTS: After intervention, the proportion of optometrists who conducted a DFE significantly increased from 79.5 (95% confidence interval [CI], 77.3 to 81.7%) to 84.4% (95% CI, 82.4 to 86.4%). In addition, the rate of improper follow-up instructions decreased from 13.8 (95% CI, 12.0 to 15.7%) to 10.8% (95% CI, 9.2 to 12.6%), and the decrease was significant ( P = .02). Although overall referrals decreased from 19.8 (95% CI, 17.6 to 21.9%) to 14.6% (95% CI, 12.6 to 16.5%), optometrists were as likely to refer to retinal specialists. Finally, concordance between documented DFE findings, assessment and plan notes, and International Classification of Diseases codes significantly increased from 78.8 (95% CI, 76.5 to 81.0%) to 88.7% (95% CI, 86.9 to 90.4%). CONCLUSIONS: Providing optometrists education in screening and assessing DR is effective in improving diabetic patient care.